Towards Rational Synthesis of Non-IPR Fullerenes Via Tandem Cyclodehydrofluorination of Fluoroarene-Based Precursors - Amsharov, Konstantin (physica status solidi (b), 2017)
In this report the successful generation of the non-isolated pentagon rule (non-IPR) fullerene fragment via regioselective cyclodehydrofluorination of a specially designed precursor under laser ionization condition is presented. It is demonstrated that the transformation of the precursor molecule to the highly strained non-IPR bowl-shaped hydrocarbon can be achieved effectively at rather low laser fluences, despite the presence of fused pentagons in the structure. This finding opens up a venue towards the rational synthesis of individual isomers of non-IPR fullerenes and other related non-IPR architectures by the bottom-up strategy. The retrosynthetic analysis of fluoroarene-based precursor molecules for non-IPR fullerenes C36–C50 is discussed.
CRIS-Team Scopus Importer:2022-04-14
Keywords: bond activation; cyclodehydrofluorination; fullerenes; laser desorption ionization; mass spectrometry; synthesis